Wheel alignment monitoring system using laser triangulation and time of flight with TCP/IP communication protocol / Mohammad Hadi Sulaiman - Sulaiman, Mohammad Hadi (2018)
A new method on wheel alignment is presented in the calibration and angle of reflection of tyres. Conventional wheel alignment monitoring system is big, bulky and limited accessible time in workshop operating hours. Hence, smaller and portable wheel alignment monitoring system is introduced in this research by using communication protocol between sensors, microcontroller and mobile phone application. The objectives of this research are to find best mounting place for the sensors from tyre in terms of distance and angle of sensors and also to design wheel alignment monitoring system which is light and portable. In this work, the light reflection theory is applied whereby the controlled factors are included in angle of reflection, camber, caster toe, mounting angle and the first position of sensors after calibration are considered. Theuncontrolled factors are included in light noise, dust noise and shaking effect. Through the experiment analysis the key factors are obtained based on the laser triangulation principle. The optimum design is completed based on the formula and calibration experiments. The result shows for laser tyre alignment system and the characteristics are established on the highest rate of changes of infrared readings from the sensor which is 60° angle. The finding also shows that higher sensitivity of infra-red setup is recommended by comparing results of infrared transmitter/receiver, constant of distance of tyre from both infra-red receiver/transmitter and constant of angle of tyre for angles. In this work, the wheel alignment is calibrated with the angle of reflection of tyres are considered and viewed on mobile application. The data from wheel alignment system is passed from the combination of receiver and transmitter connected to microcontroller to the mobile application. The TCP/IP communication protocol is applied. The controlled factors are including in data of angle of reflection, data of first time calibrated, data of current calibration, timestamp and data profile of the sensors. The uncontrolled factors such as communication delay, Wi-Fi signal and shaking effect when the vehicle is moving are also considered. The findings from the experiment analysis the key factors are obtained. The best characteristics for laser tyre alignment system relies on the highest rate of changes of infra-red readings from the sensor which is using 60 degree of angle, in other words it means higher sensitivity of infra-red setup is better. In the nutshell, early detection provided by this wheel alignment monitoring system can reduce accident by increasing the awareness or alertness of the driver regarding their vehicle alignment condition.